Entrepreneurship, Family Ties, and Land Inequality: Evidence from Italy. (11th March 2015) - Percoco, Marco
Abstract Entrepreneurship is considered to be one of the most important engines of growth, and its determinants are widely investigated. Several theories of entrepreneurship have been proposed and tested in the literature, most of them focusing on "hard factors, " i.e., determinants related to the quality/quantity of inputs and to the size of the market. In this paper, I investigate how the interaction between hard and soft factors may shape the entrepreneurial behavior of individuals. In particular, the aim of the paper is to explore the links among the structure of the family, land inequality at the beginning of the twentieth century, and subsequent entrepreneurship in Italian provinces. Using a novel data set on the Gini coefficient of land inequality in 1931, sharecropping in 1911, and the classification of family structures in 1950, I test their relevance to explaining entrepreneurship. I find that high land concentration with strong family ties reduces the probability of becoming an entrepreneur. Furthermore, the diffusion of sharecropping contracts is associated with higher entrepreneurship rates. Taken together, these results point to a central role played by the organization of agriculture in promoting entrepreneurship.